Dynamic reprogramming of the tumor immune network via multicycle checkpoint degradation for cancer immunotherapy - Tao Shi; Yuanyuan Wu; Yiran Cai; Yuting Luo; Shiji Ren; Yaning Cao; Yin Tang; Zizheng Jiang; Shiyao Hu; Wenxue Xie; Yuanyuan Chen; Lin Shen; et al. (Proceedings of the National Academy of Sciences, 2026)
The efficacy of immune checkpoint blockade is often limited by intrinsic immunosuppressive networks within the tumor immune microenvironment (TIME). Despite progress in cancer treatment, current extracellular targeted protein degradation approaches often overlook the multicellular distribution and crosstalk of immune checkpoints. Here we reported a Receptor-mediated Endolysosomal recYcling Chimera (RECYC) platform. RECYC employs a CI-M6PR-targeting aptamer that remains stable across late endosomal pH and a protein-binding peptide with moderate affinity and pH responsiveness, which together drive recycling and sustained checkpoint clearance. In ex vivo co-culture and in vivo murine models, RECYC efficiently eliminated programmed death-ligand 1 (PD-L1) expression from both tumor cells and tumor-associated myeloid cells (macrophages, neutrophils and dendritic cells). By converting an immunosuppressive TIME to an immunostimulatory state, RECYC remodeled the tumor-immune network in an anti-tumor direction, thereby enhancing CD8 + T cell response and repolarizing immunosuppressive myeloid cells. Moreover, in both immune-cold and immune-hot murine cancer models, RECYC demonstrated superior anti-tumor effect compared to PD-L1 blockade treatment. Collectively, we propose an effective strategy to induce recycling and broad checkpoint clearance in the TIME, which in turn reprograms the multicellular tumor–immune network to achieve durable immunotherapy responses.